1998
DOI: 10.1002/hlca.19980810556
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides. Part LVII.. Synthesis of phosphoramidite building blocks of 2′‐amino‐2′‐deoxyribonucleosides: New compounds for oligonucleotide synthesis

Abstract: The chemical synthesis of 2'-amino-2'-deoxyribonucleosides of uracil, cytosine. adenine, and guanine, and their conversion into suitably protected 3'-phosphoramidite building blocks 35-40 for oligonucleotide synthesis are described. The aglycone and the 2'-amino functions were protected using the 2-(4-nitrophenyl)ethoxycarbonyl (npeoc) group. The synthesis of the 3'-U-succinyl (3'-U-(3-carboxypropanoyl))-substituted starting nucleoside 41 is described and its behavior examined in solution and on solid phase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This inefficient coupling of 3, which strongly contrasts with the nearly quantitative coupling of the parent diastereoisomeric LNA amidite, [5][6][7] is probably caused by steric hindrance during the reaction between the 5A-hydroxy group of 5A-OH-T 6 and the amidite 3, the latter having three sterically demanding groups oriented towards the a-face of the furanose ring. In an attempt to improve the coupling yield of amidite 3, syntheses of 5A-X L T 6 using different activators [14][15][16] and coupling times were performed (Table 1). These experiments showed that the use of pyridine hydrochloride as activator may indeed allow efficient coupling of sterically very hindered phosphoramidite building blocks.…”
mentioning
confidence: 99%
“…This inefficient coupling of 3, which strongly contrasts with the nearly quantitative coupling of the parent diastereoisomeric LNA amidite, [5][6][7] is probably caused by steric hindrance during the reaction between the 5A-hydroxy group of 5A-OH-T 6 and the amidite 3, the latter having three sterically demanding groups oriented towards the a-face of the furanose ring. In an attempt to improve the coupling yield of amidite 3, syntheses of 5A-X L T 6 using different activators [14][15][16] and coupling times were performed (Table 1). These experiments showed that the use of pyridine hydrochloride as activator may indeed allow efficient coupling of sterically very hindered phosphoramidite building blocks.…”
mentioning
confidence: 99%
“…229 The use of the phthalimide group was also proposed; 224 the latter was introduced with high yields and could be completely removed with standard post-synthetic treatments, but in this case the condensation efficiency could be increased by only 3% ± 5%. The use of the 2-(4-nitrophenyl)ethoxycarbonyl protecting group 230,231 can hardly be called successful, since its removal demands preliminary 12-h treatment of the protected oligonucleotide with a 1 M solution of DBU in pyridine. The thus protected 2 H -amino-2 Hdeoxynucleoside cannot be immobilised on a polymeric support using a succinate linker due to intramolecular O 3 N migration of the acyl group upon deprotection.…”
Section: Solution Synthesis Of Oligonucleotide Conjugatesmentioning
confidence: 99%
“…These 2′-NH 2 and 5′- S -RNA modifications have been used independently in studies of RNA, including as mechanistic probes for ribozyme-catalyzed reactions. Many reports have described the synthesis and incorporation of 2′-amino-modified nucleosides or nucleotides into RNA, including as a photocaged precursor (Figure A,A*). Nevertheless, 2′-NH 2 substitution of the nucleophilic 2′-OH at the cleavage site of an endonucleolytic ribozyme has limited use as a mechanism probe on its own because the modification essentially abolishes cleavage. , In contrast, the inherent instability of RNA containing a 5′- S -phosphorothiolate linkage makes working with this modification more challenging (Figure B). Protection of 2′-hydroxyl with a photolabile group such as an o -nitrobenzyl group, which could be removed by UV irradiation, has facilitated the use of this modification (Figure B*). We previously developed a strategy to identify the general acid in an enzymatic reaction using sulfur substitution of the leaving group. , The better leaving ability of the sulfur obviates the need for general acid catalysis.…”
Section: Introductionmentioning
confidence: 99%